21st Joint Propulsion Conference 1985
DOI: 10.2514/6.1985-1441
|View full text |Cite
|
Sign up to set email alerts
|

Numerical calculation of subsonic jets in crossflow with reduced numerical diffusion

Abstract: A serles of calculatlons are reported for two, expenmentally studled, subsonlc Jet In crossflow geometrles. The parametrlc varlatlon examlned lnvolves the lateral spaclng of a row of Jets. The flrst serles of calculatlons corresponds to a wldely spaced Jet geometry, SID = 4, and the second serles corresponds to closely spaced Jets, SID = 2. The calculatlons are done wlth alternate dlfferenClng schemes to lllustrate the lmpact of numer1cal d1ffus1on. The calculated Jet traJectorles agreed well wlth experlmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Although a two equation k-e turbulence model was employed in these calculations, the use of a first-order accurate scheme for convection and very coarse meshes made any statements on turbulence model accuracy difficult due to the intrusion of numerical diffusion. Several solutions of the Reynolds averaged Navier-Stokes equations have already been computed for both single (Baker et al, 1982;Chien and Schetz, 1975;Harloff and Lytle, 1988;Patankar et al, 1977;Roth, 1987;Sykes et al, 1986) and multiple jets in cross flow (Claus, 1985;Demuren, 1983;Khan et al, 1981). Calculations of a turbulent jet by Patankar et al (1977) exhibit good agreement for the jet centre-line and the rate of decay of the jet velocity but deviate significantly from the experimental velocity profiles along the jet axis after the jet deflects in the reversed flow region.…”
Section: L£™g1mentioning
confidence: 96%
“…Although a two equation k-e turbulence model was employed in these calculations, the use of a first-order accurate scheme for convection and very coarse meshes made any statements on turbulence model accuracy difficult due to the intrusion of numerical diffusion. Several solutions of the Reynolds averaged Navier-Stokes equations have already been computed for both single (Baker et al, 1982;Chien and Schetz, 1975;Harloff and Lytle, 1988;Patankar et al, 1977;Roth, 1987;Sykes et al, 1986) and multiple jets in cross flow (Claus, 1985;Demuren, 1983;Khan et al, 1981). Calculations of a turbulent jet by Patankar et al (1977) exhibit good agreement for the jet centre-line and the rate of decay of the jet velocity but deviate significantly from the experimental velocity profiles along the jet axis after the jet deflects in the reversed flow region.…”
Section: L£™g1mentioning
confidence: 96%
“…These eomputetions have been compared with detailed experimental data obtained using a tvo-component phsse/Doppler technique. Prior studies which deal with some of the aforementioned issues related to the evaluation of turbulence models include the work of Leschziner and Redi (Ref 13,14), Hacliman et al (Ref 15), and Claus (Ref 16).…”
Section: Introductionmentioning
confidence: 99%
“…Childs and Nixon [27] presented calculations relevant to ground-effect flow using the k±å model and confirmed the gross features of the flow, but little comparison was given with experimental data to enable a quantitative judgement of the calculations. Claus [26] has addressed the question of false diffusion in three-dimensional jet-in-crossflow calculations and found it is necessary to adopt second-order QUICK discretization for the convective terms in order to obtain numerically accurate solutions. The k±å turbulence model with the QUICK numerical scheme was also successfully employed by Marquis [28], who concluded that the turbulent structure of the flow was independent of the velocity ratio (R jet velocity/crossflow velocity) as long as this was relatively high (of order 30).…”
Section: Introductionmentioning
confidence: 99%